Evaluation of quality parameters in ibuprofen tablets consumed in Costa Rica - Pérez López, Esteban (2020)
Based on the conditions of high demand and high consumption of ibuprofen, as well as, some news that alarms about problems generated by this drug; the present manuscript contains the evidence of the study and the results obtained for physicochemical quality tests, tested on ibuprofen tablets of different brands and doses that are consumed in Costa Rica; whose sampling in 2018 was carried out directly in shops and pharmacies in the central-western region of the country, with a view to monitoring the drug's conditions during the shelf life of the product, and providing truthful information to the public about the real state of the drug. The laboratory tests were applied in the chemistry laboratory of the University of Costa Rica in the Campus of Greece, for which official methodologies were implemented according to USP 39. The results obtained for the evaluation tests, uniformity of dosage units and Dissolution test, reflected excellent conditions for each and every one of the products involved in the study, since these are within the specifications established at the pharmacopoeial level.